PENGARUH LATIHAN KOREKSI FORWARD HEAD TERHADAP PENINGKATAN KESEIMBANGAN STATIS LANSIA DI PANTI SOSIAL X KOTA BEKASI - Sudarsono, Ari; Aminoto, Toto (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Balance is a person's ability to keep his body standing upright. Balance consists of static and dynamic balance. A person's balance is closely related to their body posture. If the body posture is not in accordance with the Line of Gravity (LOG), then the Center of Gravity (COG) shifts. COG displacement can cause a person to experience balance disorders. Forward Head Posture (FHP) is a posture disorder characterized by the head leaning forward. The aim of this research is to see the effect of forward head correction training on improving the static balance of elderly people at the X social institution in Bekasi City. The sampling technique used was purposive sampling. one group pre-post test design without a control group. The group consisted of 20 respondents. The statistical analysis used is descriptive; that is, it only looks at the description before and after training. Statistical analysis used the paired t test. The results of the study showed that there was an effect of forward head correction exercises on the balance of the elderly. These results show that after training the value is higher than before training. Thus, it can be concluded that there is an influence of forward head correction training on improving the static balance of elderly people in the X Social Home, Bekasi City.